Determination of cohesive parameters for mode II of epoxy adhesive - Kalina, Tomas (Manufacturing Technology Journal, 2020)
The paper deals with the determination of cohesive parameters of adhesive Scotch-Weld DP490 3M. Mode II of cohesive damage were examined. Experimental testing was performed on the test specimens to determine the me-chanical properties of the adhesive according to ASTM D7905. The results of the experimental testing were com-pared with the numerical simulation of the same test. The cohesive parameters of the adhesive were obtained from the numerical simulation. Cohesive parameters of adhesive can be used to design real complex adhesive bonded joints. Cohesive models (specifically cohesive contacts or cohesive elements) are one of the most accurate methods of modeling adhesive bonded joints, so this method is mainly used for parts where it is necessary to ensure suffi-cient strength, such as in automotive, aviation, etc.
Keywords: Cohesive parameters; Epoxy Adhesive; Scotch-Weld DP490 3M; Mode II; ENF